Integrative single‐cell transcriptomic analysis deciphers heterogeneous characteristics of gastrointestinal tract cancer - Chuwen Sun; Tong Li; Xin Jin; Zhihui Xiu; Hang Su; Huanming Yang; Ming Liu; Kui Wu (Clinical and Translational Medicine)
Abstract Background Gastrointestinal tract cancer (GIC), including oesophageal cancer (EC), gastric cancer (GC) and colorectal cancer (CRC), is characterised with high global incidence and mortality rates, with similar tumourigenic processes. However, the common and heterogeneous molecular features among GIC at single‐cell level remain poorly characterised. Methods Single‐cell RNA‐seq data of more than one million high‐quality annotated cells from 577 specimens, including 121 ECs, 182 GCs and 254 CRCs, were integrated to systematically decipher the heterogeneous characteristics of GIC. Non‐negative matrix factorisation (NMF) was employed to identify epithelial cell meta‐programs (MPs), and cell–cell communication analysis was conducted to investigate regulatory interactions between the tumour microenvironment (TME) and these MPs. Additionally, cell lineage inference analysis was performed to identify metaplastic signatures in EC and GC. Results We identified 24 consensus MPs from epithelial cells and 42 distinct subtypes from non‐epithelial cells thus offering a comprehensive overview of heterogeneous characteristic in GIC. Notably, we observed that EC exhibited unique features, including heightened activity in stress‐related programs and a more exhausted TME, enriched with CD4+ Tregs and CD8+ exhausted T cells. In contrast, epithelial cells in GC displayed increased expression of epithelial–mesenchymal transition (EMT)‐related signatures and an activated immune phenotype, marked by enrichment of NK cells and CD8+ effector T cells. Moreover, samples with metaplastic signatures in GC and EC showed similarities to CRC, including elevated expression of metabolism‐associated signatures and an abundance of CD4+ helper‐like T cells. Finally, we identified the potential regulatory roles of the TME in shaping epithelial cell behaviour. Conclusions Our findings provide insights into the common and specific cellular and molecular patterns associated with GIC tumourigenesis and TME remodelling. We also elucidate the similarity between GC/EC with metaplastic signature and CRC, which advancing our understanding of these malignancies. Key points A comprehensive single‐cell atlas of gastrointestinal tract cancer (GIC) was constructed. GICs exhibit distinct epithelial features and specific tumour microenvironment (TME) patterns, forming diverse niches. GC and EC exhibiting metaplastic features show elevated metabolism‐associated signatures and share similarities with CRC.